IMPLEMENTATION OF HEALTH SERVICE RIGHTS FOR VULNERABLE GROUPS IN CORRECTIONAL INSTITUTIONS - Ridhandi, Muhammad; Subroto, Mitro (Universitas Nusa Cendana, 2025)
The purpose of writing this article is to evaluate the extent of health services for vulnerable groups in correctional institutions. The method used is a literature study, which includes a comprehensive, systematic, critical, and structured review of literature related to the research topic, such as relevant articles or scientific works and legislation related to the theme. The results of the analysis show that there are various obstacles in fulfilling health services for vulnerable group prisoners, including minimal medical facilities and infrastructure, a lack of professional health workers, limited budgets in correctional institutions, no health insurance, and a lack of moral and material support from the prisoners' families. Thus, it can be concluded that health services for vulnerable group prisoners in correctional institutions are still not optimal due to various obstacles that have not found effective and efficient solutions. Keywords: Services; Health; Correctional Institutions